Organisational and advance care planning program characteristics associated with advance care directive completion: a prospective multicentre cross-sectional audit among health and residential aged care services caring for older Australians - Detering, Karen M. (BMC Health Serv Res, 2021)
BACKGROUND: Advance care planning (ACP) and advance care directive (ACD) completion improve outcomes for patients, family, clinicians and the healthcare system. However, uptake remains low. Despite increasing literature regarding organisational-level ACP characteristics leading to success, there is a lack of data measuring the impact of these factors on ACD prevalence. METHODS: A prospective multi-centre, cross-sectional audit of health records among older Australians accessing general practices (GP), hospitals and residential aged care facilities (RACF) was undertaken to describe organisational and ACP-program characteristics across services, document ACD prevalence, and assess organisation-level predictors of ACD prevalence. Organisational-level data included general and ACP-program characteristics. Patient/resident data included demographics and presence of ACDs. RESULTS: One hundred organisations (GP = 15, hospitals = 27, RACFs = 58) participated, contributing data from 4187 patient/resident health records. Median prevalence of ACDs across organisations was 19.4%, (range = 0–100%). In adjusted models, organisational sector type was the strongest predictor of ACD prevalence, with higher rates in RACFs (unadjusted 28.7%, adjusted 20.6%) than hospitals (unadjusted 6.4%, adjusted 5.8%) or GPs (unadjusted 2.5%, adjusted 6.6%). RACFs in regional and rural/remote areas had higher prevalence than metropolitan organisations. Organisations supported by government funding and those that were Not For Profit had higher prevalence than those that were privately funded, and organisations with an ACP program that had been implemented at least 3 years before data collection had higher prevalence than those with either no program or a more recent program. CONCLUSIONS: The median ACD prevalence was low, with substantial variation across organisations. Sector type was the strongest predictor, being highest in RACFs. Low prevalence rates, overall and in particular sectors, have implications for improvements. Further research into organisational factors associated with ACP/ACD completion is required.